Ascidia ceratodes (Huntsman, 1912) (Tunicata: Ascidiidae) off the northern Chilean coast: new record - Cañete Aguilera, Juan Ivan; López, José L.; Mutschke Orellana, Erika E. (My University, 2019)
ABSTRACT The ascidian fauna of northern Chile (18° to 25°S) is poorly known. A member of the family Ascidiidae, Ascidia ceratodes (Huntsman, 1912), is reported in this study. We collected samples of A. ceratodes under intertidal boulders off the northern Chilean coast between Arica (18°S) and Iquique (20°S) (17 to 20°C; intertidal pool; <0.5 m depth; August, 2016). This finding verified a questionable record established by Van Name (1945) from Tocopilla (22°S), northern Chile. This record extends the confirmed geographical distribution of A. ceratodes along of the eastern Pacific coast from British Columbia, Canada, to northern Chile.
Keywords: ascidia; warm temperate benthos; intertidal rocky shore; biodiversity; southeastern pacific